2014
DOI: 10.1093/toxsci/kfu036
|View full text |Cite
|
Sign up to set email alerts
|

Halogenated Bisphenol-A Analogs Act as Obesogens in Zebrafish Larvae (Danio rerio)

Abstract: Obesity has increased dramatically over the past decades, reaching epidemic proportions. The reasons are likely multifactorial. One of the suggested causes is the accelerated exposure to obesity-inducing chemicals (obesogens). However, out of the tens of thousands of industrial chemicals humans are exposed to, very few have been tested for their obesogenic potential, mostly due to the limited availability of appropriate in vivo screening models. In this study, we investigated whether two commonly used flame re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 37 publications
10
102
0
Order By: Relevance
“…The clones with best induction factor were selected and expanded in culture in the presence of 0.5 μg/mL puromycin. Generation of luciferase reporter cells expressing zebrafish Pparγ (HG5LN-zfPparγ cells) has been described previously (18) .…”
Section: Methodsmentioning
confidence: 99%
“…The clones with best induction factor were selected and expanded in culture in the presence of 0.5 μg/mL puromycin. Generation of luciferase reporter cells expressing zebrafish Pparγ (HG5LN-zfPparγ cells) has been described previously (18) .…”
Section: Methodsmentioning
confidence: 99%
“…Alterations of heart morphology, skeletal muscles organizations have been described in early-life BPAtreated zebrafish [125][126][127][128]. A recent study showed that zebrafish embryos exposed to BPA accumulate lipids, suggesting a role of BPA in the onset of overweight and obesity [129]. Centrally BPA treatments elicit an upregulation of AroB expression in zebrafish larvae [130,131], an estrogenic effect mediated by estrogen receptor binding and transcriptional activation [124].…”
Section: Adverse Effects Of Endocrine Disruptors During Early Neurogementioning
confidence: 99%
“…Also, long term exposure to TBT induced lipid and fatty acid accumulation in the ramshorn snail Marisa cornuarietis (Janer et al, 2007). TBT, tetrabromobisphenol-A (TTBPA), tetrachlorobisphenol-A and TTBPA-sulfate induced lipid accumulation in zebrafish larvae, which are proposed as a screening model (Tingaud-Sequeira et al, 2011;Riu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%